Factors Related to Financial Stress among College Students - Stuart Heckman; HanNa Lim; Catherine Montalto (Journal of Financial Therapy, 2014)
Concerns that debt loads and other financial worries negatively affect student wellness are a top priority for many university administrators. Factors related to financial stress among college students were explored using the Roy Adaptation Model, a conceptual framework used in health care applications. Responses from the 2010 Ohio Student Financial Wellness Survey were analyzed using proportion tests and multivariate logistic regressions. The results show that financial stress is widespread among students – 71% of the sample reported feeling stress from personal finances. The results of the proportion tests and logistic regressions show that this study successfully identified important financial stressors among college students. Two of the most important financial stressors were not having enough money to participate in the same activities as peers and expecting to have higher amounts of student loan debt at graduation. The results also indicate that students with higher financial self-efficacy and greater financial optimism about the future are significantly less likely to report financial stress. Implications for student life administrators, policymakers, financial counselors, and financial therapists are discussed.
Keywords: financial therapy; financial planning; financial counseling; student affairs; college students; financial stress; financial self-efficacy; adaptation